Pendidikan Dakwah Menggembirakan di Kalangan Generasi Muda Muhammadiyah berbasis Asset-Based Community Development - Fahma, Naomi; Syafe’i, Muhammad; Sholihah, Mar’atus; Arbaniyah, Rini (Jurnal Pengabdian Masyarakat PGSD, 2025)
The cadre of preachers needs to include knowledge of encouraging preaching methods in order to improve the capabilities and quality of preaching of young cadres. This community service activity aims to provide assistance for exciting da'wah training in the environment of the Muhammadiyah Branch Leadership (PRM) of Kadibolo Village, Klaten Regency. In the implementation of this community service using the Asset Based Community Development (ABCD) method based on 5D (Discovery, Dream, Design, Define, and Destiny) with 3 (three) stages of implementation, namely planning, action, and evaluation. The results of this activity include (1) in the planning stage begins with knowing the history of Kadibolo village, especially the Muhammadiyah profile, the management, how many residents follow Muhammadiyah, especially young cadres who will continue the generation in da'wah activities; (2) at this stage of action began to gather Muhammadiyah young people who were in the teenage category to be taught how to da'wah techniques through 3 programs, namely KAGEMBOLO, Qur’an teaching practices and parenting studies. With this da'wah training, it is hoped that young Muhammadiyah children will take turns preaching at study events; (3) the evaluation stage is more self-reflection of da'wah training activities. The results of this assistance program are shown from the emergence of awareness of da'wah by PRM cadres and then interest in spreading to peers and school-age children as a continuation of Muhammadiyah regeneration. This program has implications for a model of cadre and increased capability and success of da'wah that has an impact on the environment.